HbQ India variant in an epileptic patient – a rare case report (Indian Journal of Case Reports, 2026)
Thalassemias and structural variations such as HbS, HbE, and HbD, as well as Hb Lepore, HbD-Iran, Hb-H illness, and HbQ India, are examples of inherited hemoglobin disorders. North and West India are home to the rare alpha-chain structural hemoglobin type known as HbQ India. The majority of patients are asymptomatic, and they frequently exhibit heterozygosity or co-inherited beta-thalassemia. We present the case of a 30-year-old Indian male epileptic patient coexisting with beta-thalassemia and HbQ India heterozygous variant. This case highlights the importance of screening hemoglobin variants in beta-thalassemia, interpreting normal HbA2 in coexisting iron deficiency anemia, and recognizing anti-seizure drug effects on hematological profiles. To measure different hemoglobin, a complete blood count, peripheral blood smear analysis, and cation exchange high-performance liquid chromatography (HPLC) were performed. The HPLC chromatogram showed hemoglobin of 22.5% and a retention time of 4.39 min. The normal HbA2 despite beta-thalassemia was attributed to iron deficiency anemia. HbQ India is a rare structural variant of hemoglobin. Despite being asymptomatic, it could make diagnosing beta thalassemia in the compound heterozygous state more challenging. HPLC provides a quick, precise, and reproducible method for screening this condition, enabling the identification and guidance of affected individuals.